Implementation of Three-Dimensional Modeling & Layout in the Animation Rindu Tanah Asal - Fazril, Muhammad; Fris Okta Falma (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
In the 3D animation production process, modeling and layout serve as the fundamental basis for creating a visual narrative that supports the storyline. This final project, titled